2012
DOI: 10.1371/annotation/7f498e31-2709-44f6-877a-d0ee89bebe03
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Feasibility of Modified Surviving Sepsis Campaign Guidelines in a Resource-Restricted Setting Based on a Cohort Study of Severe S. Aureus Sepsis

Abstract: Background:The Surviving Sepsis Campaign (SSC) guidelines describe best practice for the management of severe sepsis and septic shock in developed countries, but most deaths from sepsis occur where healthcare is not sufficiently resourced to implement them. Our objective was to define the feasibility and basis for modified guidelines in a resource-restricted setting. Methods and Findings:We undertook a detailed assessment of sepsis management in a prospective cohort of patients with severe sepsis caused by a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Despite many barriers, previous work has shown that it is feasible to implement modified sepsis guidelines that are scaled to resource availability 25 . The importance of implementing a local protocol for managing children with septic shock or other sepsis-associated organ dysfunction (SSG recommendation 3) is discussed in the SSG.…”
Section: Context-specific Guidelines: a Future Directionmentioning
confidence: 99%
“…Despite many barriers, previous work has shown that it is feasible to implement modified sepsis guidelines that are scaled to resource availability 25 . The importance of implementing a local protocol for managing children with septic shock or other sepsis-associated organ dysfunction (SSG recommendation 3) is discussed in the SSG.…”
Section: Context-specific Guidelines: a Future Directionmentioning
confidence: 99%